2022
DOI: 10.48084/etasr.5394
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Reinforced Soil Shear Strength Prediction by the Analytical Approach and Artificial Neural Networks

Abstract: For the prediction of the shear strength of reinforced soil many approaches are utilized which are complex and they depend on laboratory tests and several parameters. In this study, we aim to investigate and compare the ability of the Gray and Ohashi (GO) model and Artificial Neural Networks (ANNs) to predict the shear strength of reinforced soil. To achieve this objective, this work was divided into two parts. In the first part and in order to evaluate the impact of different fiber reinforcing parameters on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the field of material modeling, some researchers [9][10][11] have used a back-propagation ANN to model the behavior of concrete in the state of plane stress under monotonic biaxial loading and compressive uniaxial cycle loading. Their findings appear to be very promising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of material modeling, some researchers [9][10][11] have used a back-propagation ANN to model the behavior of concrete in the state of plane stress under monotonic biaxial loading and compressive uniaxial cycle loading. Their findings appear to be very promising.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings appear to be very promising. Authors in [12] demonstrated the effectiveness of ANNs in characterizing composite materials. They employed a back-propagation ANN to predict composite thermal properties accurately.…”
Section: Introductionmentioning
confidence: 99%